Recent progress in cassava varietal improvement in Vietnam - Tran Ngoc Ngoan; Hoang, Kim; Kawano, Kazuo (International Center for Tropical Agriculture, 1995)
Cassava is after maize an important subsidiary crop in Vietnam. The amount of production used for human consumption is now only about 10-20 percent, that for animal feed increased to about 30 percent, for industrial processing about 30-40 percent, while about 20 percent is used for other requirements. Although in terms of area Vietnam is among the thirteen largest cassava because cassava is considered a poor farmers' crop, which is generally neglected, bot in research and in the production field. Cassava breeding for high yield and high starch content and with adaptation to adverse soil and climatic conditions is the most important among the development strategies for cassava in Vietnam. KM-60 (Rayong 60) and promising clones selected from hybrid seeds are being tested in a network of on-farm evaluation trials throught the country. This has been the result of close cooperation with CIAT since 1989. CIAT-introduced germplasm has already made a valuable contribution to the breeding program in Vietnam